Experimental study on the impacts of heatwaves with different duration and frequency on the common starfish Asterias rubens: abiotics handheld measurements - Fabian Wolf; Katja Seebass (PANGAEA, 2022)
Experimental study on the performance of the common sea star Asterias rubens subjected to heatwaves of different duration and frequency (No, Interrupted, Present-day, and Extended). Treatments are based on the climatological analysis of 22-year long temperature data. The study was conducted at GEOMAR, Helmholtz-Centre for Ocean Research Kiel (54.329979 N, 10.148013 E) in the Kiel Indoor Benthocosms (Pansch and Hiebenthal 2019) over 68 days from July 5th to September 10th, 2019. The temperature was measured with a handheld thermometer at least every three days (TTX 110 type T, Ebro, Ingolstadt, Germany). Salinity, pH, and oxygen concentration were also measured over the experimental period (Multi 3630 IDS, WTW, Kaiserslautern, Germany).
In: Wolf, F; Seebass, K (2022): Experimental study on the impacts of heatwaves with different duration and frequency on the common starfish Asterias rubens [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.939981